COMPLETE REPAIR OF TETRALOGY OF FALLOT (TOF) ON BEATING HEART SURGERY WITHOUT AORTIC CROSS CLAMPING : REPORT OF A CASE - Gerardo AK Laksono; Heroe Soebroto; Paul L Tahalele (JURNAL WIDYA MEDIKA, 2021)
Introduction: Reperfusion injury is a well-known phenomenon that occurred in cardioplegic techniques with cardiopulmonary bypass. Therefore great effort is made to prevent reperfusion injury. Beating Heart Continuous Coronary Perfusion (BHCCP) surgery is one of the alternative techniques to improve an ischemic reperfusion injury in open-heart surgery, either in pediatric or in adult. This technique can be done in complete repair of tetralogy of Fallot (TOF). Purpose: To report our first experience in doing complete repair of TOF using beating heart technique without aortic cross-clamping Case Report: A five-year-old boy came on to ER on January 6th, 2012, with a history of cyanotic since birth. His echocardiography and catheterization concluded a tetralogy of Fallot with a McGoon ratio of 1.95 (the diameter of RPA and LPA were 9.14 mm and 8.79 mm, respectively). A complete repair of TOF was done using beating heart surgery without aortic cross-clamping technique. One month post-surgery evaluation, there weren't any neurological or motor disorders. Echocardiography results showed no residual pulmonary stenosis, but 0.2 mm residual VSD was found. Conclusion: This heart rate technique is an alternative method of myocardial protection in cardiac surgery. In several cardiac centres globally, this technique is relatively safe and can be used during surgery, especially in the total correction of TOF.